From Training to Practice: Evaluating the Role and Training of Lesser Diffusion Languages Interpreters and Mediators in Healthcare Services - Jiménez Castro, María; Rivera-Trigueros, Irene (Estudios de Traducción, 2026)
This paper explores the crucial role of Lesser Diffusion Languages (LDL) Interpreters and Mediators in overcoming linguistic and cultural barriers in healthcare for migrant populations in Granada, Spain. Through a qualitative case study, it assesses the effectiveness of the Salud Entre Culturas training program in preparing interpreters for interpreting, cultural mediation, and translation services. The study draws on participant observation through detailed fieldnotes, document analysis, and surveys targeting both interpreters and healthcare professionals. These diverse data sources were brought together through a process of crystallization to provide a nuanced and comprehensive evaluation of interpreters’ practical skills, their experiences during training, and the program’s overall real-world impact within clinical settings. Findings highlight how the training equips interpreters with essential competencies that improve communication between healthcare staff and patients while also enhancing patient satisfaction and trust. The study identifies persistent challenges, including limited language-specific feedback for LDL interpreters, inconsistent access to supervisory support, and the ongoing need for continuous professional development. Recommendations include expanding language coverage, strengthening mentorship opportunities, and integrating interpreter training more fully into the public healthcare system. Additionally, the implementation of formal certification pathways would further professionalize LDL interpreters and ensure that linguistically diverse communities consistently receive high-quality, culturally responsive care. Beyond its specific findings, the study offers a replicable case-study approach grounded in crystallized data collection, which can serve as a model for evaluating LDL interpreter training programs in other multilingual and multicultural contexts.